The expanse. season three [videorecording (DVD)] - Strait, Steven, 1986-; Anvar, Cas; Tipper, Dominique; Corey, James S. A. (Universal Pictures Home Entertainment, 2018)
Hundreds of years in the future, humans have colonized the solar system. The U.N. controls Earth. Mars is an independent military power. The planets rely on the resources of the Asteroid Belt, where air and water are more precious than gold. For decades, tensions have been rising between these three places. Earth, Mars and the Belt are now on the brink of war. And all it will take is a single spark.